2023
DOI: 10.3233/shti230563
|View full text |Cite
|
Sign up to set email alerts
|

Why and When Physicians Google: Resident Physicians’ Information-Seeking Strategies During Patient Consultations

Abstract: Physicians depend on access to accurate, up-to-date information and knowledge to make decisions and carry out their work. Today, access to online medical information has become easier than ever before. There is a stream of research interested in understanding how online health information intervenes and influences the patient-physician relationship. While many studies have focused on patients’ online health information seeking, fewer studies have addressed how physicians seek and use online medical information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is particularly crucial or threatening in elds such as medicine, when confused patients attempt to associate symptoms with diagnoses and therapies. Although these models are not primarily designed for this request, the practice will nd its way into people's everyday life in a similar way to googling symptoms by both patients [8,9] and physicians [10,11]. Moreover, preliminary studies have already demonstrated signi cant potential in utilizing ChatGPT within the medical eld.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly crucial or threatening in elds such as medicine, when confused patients attempt to associate symptoms with diagnoses and therapies. Although these models are not primarily designed for this request, the practice will nd its way into people's everyday life in a similar way to googling symptoms by both patients [8,9] and physicians [10,11]. Moreover, preliminary studies have already demonstrated signi cant potential in utilizing ChatGPT within the medical eld.…”
Section: Introductionmentioning
confidence: 99%